The Influence of Protein Components on Quinoa Protein–Xanthan Gum Complex Gels at Different pH Levels - Xinxia Zhang; Yafeng Ding; Jiangtao Zhou; Qianqian Xu; Ting Li; Li Wang (Gels)
The study aimed to prepare complex gels of sonicated quinoa protein (QP) and polysaccharides, comparing the effects of different protein components and pH on gel properties. FTIR analysis demonstrated that the β-structure in protein at pH 7.0 was enhanced by ultrasonic treatment, which could promote the formation of a gel network. Moreover, XG-AG (gel prepared by xanthan gum and albumin) and XG-GG (gel prepared by xanthan gum and globulin) exhibited higher levels of disulfide bonds and free sulfhydryl groups in the gel, requiring more energy to break the intermolecular sulfide bonds during heating. Under the same heating conditions, the rheological properties and gel strength of XG-UQPG (gel prepared by xanthan gum and ultrasonically treated QP) were superior to those of XG-UGG (gel prepared by xanthan gum and ultrasonically treated globulin) and XG-UAG (gel prepared by xanthan gum and ultrasonically treated albumin). Additionally, XG-UGG (pH 7.0) demonstrated the highest water holding capacity (WHC) and oil holding capacity (OHC). This was attributed to the disulfide bonds created in the proteins by the ultrasound treatment, encouraging them to interact to form more uniform holes in gel that can hold more water/oil molecules. Conversely, at pH 4.5, the WHCs of the gels were reduced due to the presence of rougher protein structures. These findings shed light on the impact of protein composition on gel properties and offer insights into enhancing the quality of quinoa protein gel.